Labour Market Programmes and the Equity-Efficiency Trade-off - Trine Filges; John Kennes; Birthe Larsen; Torben Tranæs (Copenhagen Business School (CBS), Department of Economics, 2006)
This paper studies labour market policy in a society where differently gifted individuals can invest in training to further increase their labour market productivity and where the government seeks both effiency and equity. Frictions in the matching process create unemployment and differently skilled workers face different unemployment risks. We show that in such an environment, training programmes that are targeted to the unemployed complement passive transfers (UI benefits), unlike a general training subsidy. Combining passive subsidies with a training subsidy conditioned on the individual being unemployed (for a while) - the typical Active Labour Market Programme - implies a favorable trade-off between equity and efficiency which encourages high spending on training.
hdl:10398/7511
Keywords: H00; 330